Application of Swedish Massage for Blood Pressure in Elderly Hypertension at Karanganyar Regional Hospital - Nuraini, Oky Intan Ayu; Prajayanti, Eska Dwi; Sutarwi (Al-Hijrah Indonesia, 2023)
The aging process in the elderly affects physical changes with the emergence of degenerative diseases, namely hypertension, often found in old-age complaints. Swedish massage is a complementary therapy that can be used to reduce blood pressure in elderly hypertensives. Objectives in this study is to find out the application of Swedish massage to blood pressure in elderly hypertensives in the Mawar Room 2 Karanganyar Hospital. The research design is observational methods with research instruments using blood pressure observation sheets, SOP for Swedish Massage Techniques and digital sphygmomanometers. Respondents taken in this study were 2 elderly hypertensive patients in the Mawar Room 2 Karanganyar Hospital. The results showed that after doing Swedish Massage 3 times a day in the morning, afternoon and evening with a duration of 60 minutes, blood pressure in both respondents decreased The results of Mrs. S's blood pressure before Swedish massage therapy was 191/118 mmHg after Swedish massage therapy 3 times a day became 163/99 mmHg and for Mrs. K before Swedish massage therapy was 188/99 mmHg after Swedish massage therapy 3 times a day to 149/90 mmHg. Swedish massage is proven to help lower blood pressure in hypertensive elderly and can be recommended as complementary therapy management in improving blood pressure in hypertensive elderly in hospitals and the community.